1976
DOI: 10.1021/ja00421a034
|View full text |Cite
|
Sign up to set email alerts
|

1H-Benzazirines. Intermediates in the ring contraction of iminocyclohexadienylidenes and arylnitrenes

Abstract: Communications to the Editor lti-Benzazirines. Intermediates in the Ring Contraction of Iminocyclohexadienylidenes and Arylnitrenes1Sir:Recent work on oxocarbenes,2 thioxocarbenes,3 and imi-nocarbenes4 has demonstrated that the Wolff rearrangements in these species are often preceded by isomerization to oxirenes, thiirenes, and l//-azirines, respectively. How-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 8 publications
1
39
1
Order By: Relevance
“…An arene aziridine is also observed (ion c), which arises from a second loss of CO [544][545][546] . The ions b and c are also observed in the gas-phase pyrolysis of isatin 547 . In a general manner, the mass spectra of 3-substituted isatins show a sequential loss of neutral molecules 548 (Scheme 135).…”
Section: Mass Spectrometrymentioning
confidence: 89%
“…An arene aziridine is also observed (ion c), which arises from a second loss of CO [544][545][546] . The ions b and c are also observed in the gas-phase pyrolysis of isatin 547 . In a general manner, the mass spectra of 3-substituted isatins show a sequential loss of neutral molecules 548 (Scheme 135).…”
Section: Mass Spectrometrymentioning
confidence: 89%
“…Labelling experiments have demonstrated that, in fact, all ring carbon atoms in cyanocyclopentadiene become completely scrambled due to these rapid sigmatropic shifts of H and CN. [41] Napthyl Azides ] Naphthylnitrenes A mixture of 2-and 3-cyanoindenes 17 and 16 is obtained on FVT of 1-and 2-naphthyl azides 8 and 22 as well as the triazoles and tetrazoles 10, 11, 21, and 24 at 340-4008C (Scheme 2). The triazoles and tetrazoles have been shown to be precursors of quinolyl-and isoquinolylcarbenes, which rearrange to the 1-and 2-naphthylnitrenes via ring expansion to cyclic carbodiimides 12 and 19.…”
Section: Phenyl Azide ] Phenylnitrene ] Cyanocyclopentadienementioning
confidence: 99%
“…It is generally accepted that [Mn(CO) 5 ]· radicals are generated by the photolysis or thermolysis of [Mn 2 (CO) 10 ]. 26,27 In addition, cyclopropabenzenes reportedly decompose by the thermolysis 1 -3,28,29 and photolysis 30 to generate the corresponding biradical via the C-C bond cleavage in the cyclopropene ring.…”
Section: Thermal Reaction Of 1 With [Mn 2 (Co) 10 ]mentioning
confidence: 99%
“…heavier congeners of cyclopropane and cyclopropene. 7 -9 However, the chemistry of heteroatom analogs of cyclopropabenzene has been unexplored because of their low thermal stability except for some examples of heteracyclopropabenzenes such as aza-, 10 thia-, 11,12 selena-, 13 bora-, 14 and silacyclopropabenzenes 15 postulated as reactive intermediates. On the other hand, we have recently succeeded in the synthesis of the first stable sila- 16,17 and germacyclopropabenzenes, 18 by taking advantage of a combination of efficient steric protection groups, 2,4,6-tris[bis(trimethylsilyl)methyl]phenyl (Tbt) and 2,6-diisopropylphenyl (Dip), via the reactions of the corresponding overcrowded dilithiosilane 19 and dilithiogermane 18 with o-dibromobenzene, respectively.…”
Section: Introductionmentioning
confidence: 99%